Kontribusi Muhammad Ajjaj al-Khatib dalam Studi Hadis: Telaah Terhadap Kitab al-Sunnah Qabl al-Tadwin dan Ushul al-Hadits - Farida, Umma (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2022)
The discourse on the authenticity of hadith is very crucial in hadith studies, which has been the subject of study for both previous and contemporary hadith scholars. This article aims to describe the thoughts of one of the contemporary hadith scholars, Ajjaj al-Khatib, and his contribution to the study of hadith. This research is literature research by focusing the study on the two works of al-Khatib, namely al-Sunnah Qabl al-Tadwin and Ushul al-Hadith. The data collected through the documentation technique was then analyzed descriptively-critically. The research results show that al-Khatib has hadith thoughts that are in line with the mainstream of the muhadditsin regarding general rules in the science of hadith. He explains the discussions in hadith studies in a meaningful language systematically and easy to be understood, straightens the contradiction about the writing and codification of hadith, hadith falsification, and the capacity of companions and tabi'in in the transmission of hadith comprehensively. Apart from that, he also contributed to explaining the historical roots of hadith that were valid since the time of the Prophet, as well as discussing and refuting the ideas of the orientalists with verbal and rational arguments.